The Relationship Between Levels of Knowledge, Perception, and Attitude With Cervical Cancer Prevention Behavior Through Hpv Vaccination Among Female Medical Students of The Faculty of Medicine, Islamic University of Al-Azhar - Ayu Adelia Kristiani Putri, Kadek; Putu Dedy Arjita, I; Santosa, Hilda; Ashabul Kahfi Mathar, Muhammad (International Journal of Health and Pharmaceutical (IJHP), 2026)
Background: Cervical cancer is a women's reproductive health problem that can be prevented through Human Papillomavirus (HPV) vaccination. However, HPV vaccination coverage among young age groups, including female medical students, remains relatively low despite their health education background. Knowledge, perceptions, and attitudes are believed to play a role in shaping health-related behaviors. Objective: To analyze the relationship between the level of knowledge, perceptions, and attitudes with cervical cancer prevention behavior through HPV vaccination among female medical students at Al-Azhar Islamic University Methods: This study used a quantitative cross-sectional design. A total of 75 female medical students were selected using proportionate stratified random sampling. Data were collected through a structured questionnaire and analyzed using the Chi-square test with a significance level of p-value < 0.05. Results: The majority of respondents had good knowledge, positive perceptions, and favorable attitudes toward cervical cancer and HPV vaccination. However, most respondents had not received the HPV vaccine (85.3%). Statistical analysis showed no significant association between knowledge (p = 1.000), perception (p = 0.056), or attitude (p = 1.000) and cervical cancer prevention behavior through HPV vaccination. Conclusion: Good levels of knowledge, perception, and attitude were not significantly associated with cervical cancer prevention behavior through HPV vaccination among female medical students.